Yemen, Republic of - Urban Transport in Sana’a : Strategy Note - World Bank (World Bank, 2012)
Yemen, the fastest urbanizing country in the Middle East and North Africa region, has a very limited natural resource base and the efficiency of its cities is therefore essential for its future economic growth. However, this efficiency is increasingly handicapped by the poor performance of urban transport, especially in the capital Sana'a. This report presents the main findings of this review and makes key recommendations to improve the efficiency of urban transport in Sana'a. It contains the following chapters: a first chapter presents the general context of the study, characterized by fast demographic and spatial growth in Sana'a, causing major difficulties in terms of urban transport management; a second chapter analyses and describes the main underlying issues affecting the performance and efficiency of Sana'a transport system; a third chapter presents institutional, technical and financing recommendations to improve the performance of Sana'a transport system; and a fourth chapter presents a tentative three-year action plan for implementation of the recommendations.